A 2022 vision of offshore engineering professionals on the application of agile methodologies - Andrade , Bruno Rodrigues de; Mainier , Fernando B.; Monteiro, Paulo Roberto Duailibe (Seven Editora, 2023)
It has been observed the recognized effectiveness of the use of Agile Methodologies in Information Technology (IT) projects and the discreet application of these methodologies in Engineering projects. The present work aims to carry out a study of the use of Agile Methodologies in the design and manufacturing phases of offshore equipment, allowing the profile of the population most familiar with these methodologies to be drawn, as well as to seek information regarding their implementation. For the development of this study, a questionnaire elaborated with nineteen questions was sent to one hundred and seventy respondents, in addition to conducting interviews with seven of these respondents, which allowed, thus, to gather information about the area of activity, the level of education, the age, years of experience of the respondents, among other information, characteristics, and aspects. In conclusion, this study manages to draw a parallel between the use of Traditional and Agile Methodologies, indicating which are the most used and informing the perception of professionals regarding the use of these methodologies. DOI:https://doi.org/10.56238/alookdevelopv1-070